Treatment of condylar fractures with an intraoral approach using an angulated screwdriver: Results of a multicentre study - Vajgel, André; Santos, Thiago de Santana; Camargo, Igor Batista; Oliveira, David Moraes; Laureano Filho, José Rodrigues; Vasconcellos, Ricardo José de Holanda; Lima Júnior, Sergio Monteiro; Pereira Filho, Valfrido A. [UNESP]; Mueller, Andreas A.; Juergens, Philipp (Elsevier, 2015)
Background This multicentre study aimed to investigate long-term radiographic and functional results following the treatment of condylar fractures using an angulated screwdriver system and open rigid internal fixation with an intraoral surgical approach. Methods Twenty-nine patients with a total of 32 condylar fractures were evaluated. The patients were investigated prospectively based on the following variables: age, sex, aetiology, side, location and classification of the fracture, degree of displacement, associated fractures, surgical approach, oral health status, type of osteosynthesis plate, duration of surgery, mouth-opening, complications, and duration of follow-up. Results The fractures were classified as subcondylar (n = 25) or condylar neck (n = 7). Mean patient age was 36.38 ± 16.60 years. The median duration of postoperative follow-up was 24.39 ± 13.94 months. No joint noise, weakness of the facial nerve, joint pain, or muscle pain was observed. An additional retromandibular approach was necessary to enable the treatment of one subcondylar fracture with medial displacement. Conclusion Subcondylar or condylar neck fractures with medial or lateral displacement can be treated using an intraoral approach with satisfactory results with the advantages of the absence of visible scarring, the avoidance of facial nerve injury, and the ability to obtain rapid access to the fracture.
Keywords: Intraoral approach; Mandibular condyle; Open treatment